Sistem Informasi Pengolahan Data Atlet Berbasis Web Pada Disporabudpar Tangerang - Padeli Padeli; Gustina Gustina; Muhammad Fiqih Firmansyah (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2022)
Information system needs cover almost all areas of life. Accurate, fast, and relevant information is needed in organizations. But in reality, due to the lack or limited use of information systems, sometimes it is not in sync with the wishes and expectations that are to be realized. Disporabudpar Tangerang Regency is an organization that needs to develop information technology that can change its data processing. The athlete data processing system at Disporabudpar is still in the form of manual files using documents and the stored data is still in the form of Ms. Word and Excel. This can slow down the process of inputting and processing data as well as the risk of errors and inaccuracies in writing which can cause the reporting process to take a lot of time. The research analysis method uses Waterfall and Unified Modeling Language (UML) as a design method based on the PHP programming language with MySQL database. Due to the above, a web-based athlete data processing information system is needed to be implemented at the Tangerang Disporabudpar.